Assessment of Safe Cartilage Harvesting Quantity in the Shoulder: A Cadaveric Study - Michael C. O'Brien, B.S., M.A; Wojciech K. Dzieza, B.S; Michelle L. Bruner, M.S; Kevin W. Farmer, M.D (Elsevier, 2021)
Purpose: To evaluate the volume and yield of morselized cartilage that can be harvested from the shoulder for immediate reimplantation and repair. Methods: A standard arthroscopic approach was used to harvest non-load-bearing cartilage from 5 cadaveric shoulder specimens. Cartilage was separated from the humerus, grasped, added to the cartilage particulator, and morselized to form a cartilage paste. The volume of reclaimed cartilage was measured and compared with average humeral and glenoid defects. Results: The total yield of cartilage paste following tissue processing that was obtained from the 5 glenohumeral joints ranged from 1.0 mL to 2.4 mL with a mean volume of 1.9 ± 0.5 mL, yielding a theoretical 18.6 cm2 ± 5.2 cm2 of coverage with a 1-mm monolayer. Previously reported mean glenoid defect size ranges from 1.12 cm2 to 2.73 cm2, while the mean humeral defect size ranges from 4.22 cm2 to 6.00 cm2. Conclusions: This study validated that through a single-stage surgical and processing technique it is possible to obtain a sufficient volume for re-implantable autologous morselized cartilage graft to address most glenohumeral articular cartilage defects. Clinical Relevance: Chondrocyte grafts have been shown to be effective in cartilage repair. A single-site, single-staged procedure that uses a patient's autologous shoulder cartilage from the same joint has the potential to reduce morbidity associated with multiple surgical sites, multistaged procedures, or nonautologous tissue in shoulder surgery.